ESSENTIAL APPROXIMATE POINT AND ESSENTIAL DEFECT SPECTRUM OF A SEQUENCE OF LINEAR OPERATORS IN BANACH SPACES - TOUFIK, HERAIZ (Université de M'sila, 2019)
This paper is devoted to an investigation of the relationship between the essential approximate point spectrum (respectively, the essential defect spectrum) of a sequence of closed linear operators (Tn)n2N on a Banach space X, and the essential approximate point spectrum (respectively, the essential defect spectrum) of a linear operator T on X, where (Tn)n2N converges to T, in the case of convergence in generalized sense as well as in the case of the convergence compactly